Social Control or Public Image, When Mass Media and University-Owned Media Construct Narratives of Sexual Violence - Theresia Intan Putri Hartiana; Putra Aditya Lapalelo; Nanang Krisdinanto (Jurnal Komunikasi, 2023)
Sexual violence in higher education is a sensitive topic as well as a topic that attracts the most media attention. For example, in early 2022, the Dean of one of the faculties at Riau University (UNRI) was suspected of harassing his students during the implementation of final project guidance. Since it was reported, this case has grabbed attention, appeared in the corners of social media discussions, and become a discourse in the mass media. Many media outlets, especially online media, have attempted to revisit the public's memory of sexual violence cases in Indonesia's higher education environment, and how these campuses have handled the issue of sexual violence. On the other hand, several universities in Indonesia have tried to show their 'concern' for cases of sexual violence that have occurred in Indonesian universities through campus "news" portals. The question that arises then is whether the media concern narrated in media portal news and campus concern in campus portal news are similar forms of concern. This research tries to answer this question by managing the news of media portals and campus portals in relation to the news of sexual violence in the campus environment using a qualitative approach with a narrative analysis method by utilizing a narrative model developed from the thoughts of Todorov (1977) to define the structure and plot of news narratives, and Propp (1968) to dissect the construction of meaning through characterization. By looking at the structure and characterization in news narratives, it is hoped that it can answer how the phenomenon of sexual violence is narrated by media portals and campus portals and what interests are behind the news narratives of sexual violence published by media portals and campus portals.